How do socially responsible universities perform? the case of Spanish universities - Arias-Valle, María Belén (2021)
University Social Responsibility (USR) is a strategic management approach whose introduction in universities’ mission statement is encouraged by international organizations (e.g., United Nations (UN) and the United Nations Educational, Scientific and Cultural Organization (UNESCO)), as well as by public administrations. Universities are increasingly responding to this demand by incorporating USR principles and sustainable development in their practices and daily activities. This study aimed to identify the strategic profile of socially responsible universities (based on their institutional mission statement). To achieve this goal, qualitative comparative analysis was applied to the case of the Spanish higher education system. The findings confirm the initial intuition about the heterogeneous nature of the strategic patterns followed by Spanish universities. In order to respond to the international calls for incorporating social responsibility principles into their culture, Spanish universities adopt different strategies that affect the four areas that shape their organizational scope.